The uncertain path from good intentions to actual behavior: A field study on mobile app usage - Tiefenbeck, Verena; Kupfer, Anna; Ableitner, Liliane; Schöb, Samuel; Fleisch, Elgar; Staake, Thorsten (Twenty-First DIGIT Workshop, 2016)
In the domain of energy consumption, good intentions do not necessarily imply sustainable behavior. Information Systems (IS) can promote energy efficiency by providing users with information about their behavior. While IS research has developed several models explaining adoption and usage of various technologies in the organizational context, less is known about the adoption of IS in the consumer context. We examine usage behavior of a sustainability smartphone application in a large-scale field study applying the Unified Theory of Acceptance and Use of Technology (UTAUT). Our data, collected in two surveys and from server log data, suggests that users do not follow through on their good intentions: while intention is indeed well explained by UTAUT factors, it does not necessarily predict usage. Moreover, we find only a mild correlation of self-reported usage and log data. The results highlight the need to better understand adoption and usage of I